EMPOWERING MSMES THROUGH THE USE OF DIGITAL MARKETING IN IMPROVING HALAL PRODUCTS AND TOURISM IN THE CITY OF LHOKSEUMAWE - Damanhur, Damanhur; Ichsan, Ichsan; Fauzul Hakim Hasibuan, Ahmad; Ridani Alifah, Syarifah; Nurmalita Sari, Dina (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2021)
Souvenir business is a business that has been running in Lhokseumawe City from several decades back, tourist interest in merchandise and souvenirs when visiting Aceh province, especially Lhokseumawe city is a special attraction when shopping. This city is a vital route of distribution and trade in Aceh. But this has not been supported using technology in the development of digital marketing management. The solution to partner problems is by fostering business management, developing human resources, conducting coaching regarding the promotion of partner products, motivating employees and mastering technology. The outputs in this service for the year are: 1. Draft Scientific Publications in the Journal of Community Service Darma Bakti Teuku Umar 2. Serambi Indonesia Mass Media Articles 3. Increasing Partner Capabilities by Optimizing Digital Marketing.